2015
DOI: 10.1155/2015/178618
|View full text |Cite
|
Sign up to set email alerts
|

Neural Differentiation of Human Adipose Tissue-Derived Stem Cells Involves Activation of the Wnt5a/JNK Signalling

Abstract: Stem cells are a powerful resource for cell-based transplantation therapies, but understanding of stem cell differentiation at the molecular level is not clear yet. We hypothesized that the Wnt pathway controls stem cell maintenance and neural differentiation. We have characterized the transcriptional expression of Wnt during the neural differentiation of hADSCs. After neural induction, the expressions of Wnt2, Wnt4, and Wnt11 were decreased, but the expression of Wnt5a was increased compared with primary hADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…These observations suggest that the WNT pathway is turned off and differentiation of MSCs is induced by JQ1. This is in partial agreement with a previous report where downregulation of WNT2 , FZD2 , and FZD4 and upregulation of CTNNB1 was involved in neural differentiation of human adipose-derived stem cells [ 49 ]. Taken together, these observations suggested that JQ1 modulates WNT signaling, which is known to be involved in self-renewal and differentiation of MSCs.…”
Section: Discussionsupporting
confidence: 93%
“…These observations suggest that the WNT pathway is turned off and differentiation of MSCs is induced by JQ1. This is in partial agreement with a previous report where downregulation of WNT2 , FZD2 , and FZD4 and upregulation of CTNNB1 was involved in neural differentiation of human adipose-derived stem cells [ 49 ]. Taken together, these observations suggested that JQ1 modulates WNT signaling, which is known to be involved in self-renewal and differentiation of MSCs.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, it was shown that Wnt1 upregulates Tlx3, and a forced expression of Tlx3 improved neurogenic differentiation [89]. Wnt5a promoted neurogenic differentiation in human ADSCs, binding to Fz3 and Fz5, and signalling through the Wnt5a-JNK pathway [90]. In summary, activation of Wnt signalling plays a key role in promoting the differentiation of MSCs towards a neuronal fate.…”
Section: Accepted Manuscriptmentioning
confidence: 63%
“…10,11 Recent studies in the adult CNS after injury demonstrate that canonical Wnt signaling induces axonal regeneration and neurite growth, suggesting that the developmental role for Wnt can be repurposed in adults by exogenous stimulation of the pathway. Non-canonical Wnt signaling including Wnt/ Ryk, Wnt/Ca + , and Wnt/JNK pathways have been reported to have a positive effect in neural differentiation, [18][19][20] but the further mechanism in promoting neural differentiation is unclear. 16 These two Wnt target genes are suppressed by the Notch effectors Hes1 and Hes5, leading to a competition between stem cell maintenance caused by Notch signaling and differentiation caused by Wnt signaling.…”
mentioning
confidence: 99%